Analysis of indexes exceeding water quality standards in the Yangtze River basin during the 13th Five-Year Plan period. Issue 1 (February 2021) - Lin, Lanyu; Zhou, Mi; Yan, Luyu; Lv, Xin; Zhang, Fengying
Abstract: Based on monitoring data from 615 comparable sections of the Yangtze River Basin (YRB) in the national eco-environmental monitoring network during the 13 th Five-Year Plan period, the spatiotemporal characteristics of Total phosphorus (TP), Ammonia nitrogen (NH3 - N), and Chemical oxygen demand (COD) were analyzed. The results showed that during the study period, the overall pollution of the main rivers in the YRB had been mitigated, and the measured amounts of TP, NH3 -N, and COD had decreased. However, the annual concentrations of TP, NH3 -N, and COD had increased in nearly one-third of the sections, and in some sections they increased greatly. Increased TP was mainly observed in the provinces of Shaanxi, Sichuan, Hunan, and Hubei. Increased NH3 -N was mainly observed in Hubei and Sichuan, and increased COD was mainly observed in Hunan, Sichuan, Hubei, and Shanghai. Since the first year of the 13 th Five-Year Plan, the water quality of the main rivers in the YRB has continuously improved; however, in some sections the concentrations of some indexes already above water quality standards increased sharply. Under the protection strategy of the Yangtze River Economic Zone, the 14 th Five-Year Plan will emphasize requirements for ecological environmental protection to improve the water quality in the YRB.